The LongitudinAl Nationwide stuDy on Management And Real‐world outComes of diabetes in India over 3 years ( LANDMARC trial) - Das, Ashok K.; Kalra, Sanjay; Joshi, Shashank; Mithal, Ambrish; Kumar, K. M. Prasanna; Unnikrishnan, A. G.; Thacker, Hemant; Sethi, Bipin; Chowdhury, Subhankar; Sugumaran, Amarnath; Satpathy, Ashwini; Gadekar, Arvind; et al. (Endocrinology, diabetes & metabolism, 2023)
The 3‐year data from the longitudinal LANDMARC study provide valuable insights on diabetes‐related complications, disease progression and treatment strategies among people with diabetes in India. In this pan‐India study, at the end of 3‐years, 205 (3.29%) and 1121 (18.02%) participants reported macrovascular and microvascular complications, respectively, with nonfatal myocardial infarction (40.0%; n = 82) and neuropathy (81.98%; n = 919) being the most common complications. Despite a gradual improvement in glycemic levels, the burden of uncontrolled glycemia (HbA1c > 7%) was considerable (63.4%; n = 2344). The LANDMARC study emphasizes the need for optimizing disease management and timely intensification of therapy among people with diabetes in India.